A BRIEF REVIEW ON THE ADVANTAGES, HINDRANCES AND ECONOMIC FEASIBILITY OF STIRLING ENGINES AS A DISTRIBUTED GENERATION SOURCE AND COGENERATION TECHNOLOGY - Delgado Filho, M. A.; F. T. S. Araújo, N. M.; Maia, F. P.; Medina Tapia, G. I. (Revista de Engenharia Térmica, 2018)
The present paper aims to provide a brief review of the potentiality and economic feasibility of the Stirling engine as a distributed generation source and cogeneration technology. Another objective was the determination of hindrances which may be preventing the feasibility of the Stirling technology. With these intentions, a research based on a combination of preselected keywords was performed at the Metasearch of CAPES (Brazil's Higher Education Coordination of Personnel Perfecting). No filters in relation to the research period or to particular geographical regions were employed, thus publications until 2017’s middle were included and the research was conducted on a global level. Next, the selection of papers which contained some of the keywords was made, consisting initially of the read of the publications’ abstracts. The remaining ones were then further explored and had their relevant information incorporated, according to the scope of this work. It is worth mentioning that other accredited sources which dealt with important aspects of the topic were also included. Furthermore, a table containing some examples of products concerning the application of the Stirling engine as a distributed generation and cogeneration technology is presented. Ultimately, it is concluded that the Stirling technology, despite its advantages and suitability regarding the proposed applications, is not yet commercially feasible, having currently only a minor presence in the market. This scenario can be attributed to the need for further research and technical development as well as cost reduction.